2014
DOI: 10.1902/jop.2014.130523
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of Candidate Genes for Periodontitis Using Multiple Computational Tools

Abstract: A combination of computational tools will be useful in mining candidate genes for periodontitis. These theoretical results provide new clues for experimental biologists to plan targeted experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 64 publications
0
40
0
Order By: Relevance
“…13 MMP7 upregulation that we found, support the knowledge of previous functional studies. [16][17][18][19] As a result of our data we found tumor necrosis factor receptor superfamily member 17 (TNFRSF17), Fc receptor-like 5 (FCRL5), marginal zone B and B1 cell-specific protein (MZB1) ve desmocollin-1 (DSC1) genes presented significant expression differences. In our study group, TNFRSF17, FCRL5 and MZB1 genes were upregulated, where as DSC1 gene was downregulated.…”
Section: Discussionmentioning
confidence: 65%
“…13 MMP7 upregulation that we found, support the knowledge of previous functional studies. [16][17][18][19] As a result of our data we found tumor necrosis factor receptor superfamily member 17 (TNFRSF17), Fc receptor-like 5 (FCRL5), marginal zone B and B1 cell-specific protein (MZB1) ve desmocollin-1 (DSC1) genes presented significant expression differences. In our study group, TNFRSF17, FCRL5 and MZB1 genes were upregulated, where as DSC1 gene was downregulated.…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, in vitro investigations demonstrated that periodontitis-associated bacterial DNA upregulates several genes of the innate immune response and induces the production of proinflammatory cytokines through TLR9 in macrophages and epithelial cells (20)(21)(22). In fact, a recent study has identified the TLR9 gene as one of the most promising candidate genes involved in the pathogenesis of periodontitis by using an integrative gene prioritization method (23). Collectively, emerging evidence suggests that TLR9-triggered immune responses may constitute a novel inflammatory pathway in periodontitis (24).…”
mentioning
confidence: 99%
“…Three genes that were prioritized in the Zhan et al (2014) ). Noteworthy, VAV1 had been prioritized by the parent single-marker GWAS for its association with moderate CP, and its gene-centric association in the present analysis had a p value of 4.4 × 10 -5 .…”
Section: Gene-centric Association Analysis Resultsmentioning
confidence: 99%
“…We used LocusZoom 1.1 (Pruim et al, 2010) to visualize the genes and loci of interest. We additionally examined genes that were previously implicated in CP (Laine et al, 2012) or were prioritized via bioinformatics tools (Zhan et al, 2014). A comprehensive list of all genes' association results was also generated and has been made available at the http://genomewide.net online repository with links provided in the results section.…”
Section: Gene-centric Association Testingmentioning
confidence: 99%